2021
DOI: 10.7150/jca.58182
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of the Interactions between Circular RNAs and RNA-binding Proteins in Common Human Cancers

Abstract: Circular RNAs (circRNAs) are a unique family of noncoding RNAs that could regulate multiple biological processes, which play a crucial role in carcinogenesis, progression and chemotherapy resistance of cancers. Growing studies have demonstrated that circRNAs act as novel biomarkers and therapeutic targets for cancers by sponging microRNAs (miRNAs). Up to date, another function of circRNAs, combining with RNA-binding proteins (RBPs), was uncovered. However, there is limit studies illustrating the underlying mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 111 publications
2
10
0
Order By: Relevance
“…To date, circRNAs have been proposed to function through several molecular mechanisms, including (i) miRNA sponging, (ii) mRNA regulation at both translational and transcriptional levels, (iii) interacting with proteins to form circRNA-protein complexes, and (iv) translation into a peptide or a protein 84 - 86 . However, circRNA binding to mRNA and proteins is often taking place at odds and not always concordant.…”
Section: Functional Mechanisms Of Circrnas Associated With Hippo-yap ...mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, circRNAs have been proposed to function through several molecular mechanisms, including (i) miRNA sponging, (ii) mRNA regulation at both translational and transcriptional levels, (iii) interacting with proteins to form circRNA-protein complexes, and (iv) translation into a peptide or a protein 84 - 86 . However, circRNA binding to mRNA and proteins is often taking place at odds and not always concordant.…”
Section: Functional Mechanisms Of Circrnas Associated With Hippo-yap ...mentioning
confidence: 99%
“…However, circRNA binding to mRNA and proteins is often taking place at odds and not always concordant. Interestingly, most of the studies involving circRNAs have been in the field of cancer 21 , 84 , 87 . Thus far, only a handful of studies have reported about the circRNAs regulating the Hippo-YAP signaling pathway.…”
Section: Functional Mechanisms Of Circrnas Associated With Hippo-yap ...mentioning
confidence: 99%
“…Numerous previous studies have shown that circRNAs can exert their functions by binding to and acting on proteins, especially RNA-binding proteins (RBPs) by functioning as a sponge, decoy, or scaffold [ 43 , 44 ]. To understand the mechanism by which the hsa_circ_0062682 exerts its oncogenic potential in HCC we wanted to investigate potential protein binding partners.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from miRNAs, circRNAs also regulate target mRNAs and their translation by sequestering RNA binding proteins (RBPs) [ 84 ]. However, little is known on the role of circRNA-RBP interactions in promoting invasion and metastasis in cancer [ 85 ]. In a recent study, a novel circRNA, circ0005276, was shown to enhance cell proliferation, EMT, and migration in prostate cancer by interacting with FUS RBP.…”
Section: Molecular Homeostasis Signaling In Cancer Hallmarksmentioning
confidence: 99%